A new role for FBP21 as regulator of Brr2 helicase activity. Issue 13 (27th June 2017) - Henning, Lisa M.; Santos, Karine F.; Sticht, Jana; Jehle, Stefanie; Lee, Chung-Tien; Wittwer, Malte; Urlaub, Henning; Stelzl, Ulrich; Wahl, Markus C.; Freund, Christian
Abstract: Splicing of eukaryotic pre-mRNA is carried out by the spliceosome, which assembles stepwise on each splicing substrate. This requires the concerted action of snRNPs and non-snRNP accessory proteins, the functions of which are often not well understood. Of special interest are B complex factors that enter the spliceosome prior to catalytic activation and may alter splicing kinetics and splice site selection. One of these proteins is FBP21, for which we identified several spliceosomal binding partners in a yeast-two-hybrid screen, among them the RNA helicase Brr2. Biochemical and biophysical analyses revealed that an intrinsically disordered region of FBP21 binds to an extended surface of the C-terminal Sec63 unit of Brr2. Additional contacts in the C-terminal helicase cassette are required for allosteric inhibition of Brr2 helicase activity. Furthermore, the direct interaction between FBP21 and the U4/U6 di-snRNA was found to reduce the pool of unwound U4/U6 di-snRNA. Our results suggest FBP21 as a novel key player in the regulation of Brr2.